Laugier-Hunziker Syndrome - Vacas, Aldana Soledad; Cabarcas Avila, Freddy; Bollea Garlatti, María Luz; Enz, Paula; Kowalczuk, Alicia M. (Revista del Hospital Italiano de Buenos Aires, 2016)
Laugier-Hunziker syndrome is a rare acquired pigmentary disorder that is characterized by idiopathic mucocutaneous pigmentation that may be associated with longitudinal melanonychia. Although this syndrome is considered a benign disease with no systemic manifestations or malignant potential, it is important to rule out other mucocutaneous pigmentary disorders, especially Peutz-Jeghers syndrome. We report the case of a patient with this unusual syndrome
Keywords: Laugier-Hunziker syndrome; melanonychia; pigmentary disorder; lentiginosis